STUDY OF THE SPECTRAL PROPERTIES OF THE DISELENIUM DICHLORIDE (Se2Cl2) MOLECULE IN THE I. R. INFRARED AREA - Hadeer Mohammed Farhan; Ahmed Mohammed Farhan; Dakhil A. Abdzaid (European Science Publishing, 2025)
The spectral and thermal properties of (Selenium-Halogen (Se2Cl2)) have been studied in this study, where the spatial geometry of the particles was studied using semi-experimental quantum programs in methdd (MNDO/PM3) via the dimensions of bonds. The basic molecule vibration frequencies, which have six basic vibration frequencies ranging from (69.34 - 456.01) cm-1 in the chair-form state, were also measured. The power is equal to (E.A = 2.047253eV), (Eg = 1.655715eV) and the distance quantity was determined to measure electronic affinity (E.A). The energy levels were then represented by two-dimensional ( 2D) and three-dimensional ( 3D) diagrams, and the total particle charge density and electrostatic voltage were determined using the HYPERCHEM software for most of the previous readings.
Keywords: Spectral, Selenium, Halogen, HYPERCHEM 6, MNDO / pm3, molecular orbitals.